The making of medieval Sardinia - Metcalfe, Alex 1967-; Fernández-Aceves, Hervin; Muresu, Marco 1987- (The medieval mediterranean, 2021)
This landmark volume combines classic and revisionist essays to explore the historiography of Sardinia's exceptional transition from an island of the Byzantine empire to the rise of its own autonomous rulers, the iudikes, by the 1000s.